Implementasi Tempat Sampah Pintar Berbasis Internet of Things: Studi Kasus: Warung Sembako Desa Blambangan - Raihan Eka Prasetyo; Yusuf Eko Rohmadi; Muhammad Abdul Aziz (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
The development of Internet of Things (IoT) technology provides a solution to improve the efficiency of real-time monitoring, including in waste management. At the Stall of Grocery Store in Blambangan Village, monitoring the condition of the trash bin is still done manually, resulting in frequent delays in determining the level of fullness of the trash, which can cause accumulation and reduce environmental cleanliness. This study aims to implement an IoT-based smart trash bin to automatically monitor trash capacity and send notifications to users. The research methods used include observation, needs analysis, system design, implementation, and testing. The system was developed using an HC-SR04 ultrasonic sensor as a trash capacity detector, an ESP8266 microcontroller as a data processor and internet connection, and the Blynk application as a monitoring medium. The results of the study show that the system is able to monitor the level of fullness of the trash in real-time and send automatic notifications when the trash capacity reaches a predetermined limit. This system helps improve monitoring effectiveness, prevent waste accumulation, and support environmental cleanliness at the Stall of Grocery Store in Blambangan Village.